Role of stem cells during diabetic liver injury. Issue 2 (9th December 2015) - Wan, Ying; Garner, Jessica; Wu, Nan; Phillip, Levine; Han, Yuyan; McDaniel, Kelly; Annable, Tami; Zhou, Tianhao; Francis, Heather; Glaser, Shannon; Huang, Qiaobing; Alpini, Gianfranco; et al.
Abstract: Diabetes mellitus is one of the most severe endocrine metabolic disorders in the world that has serious medical consequences with substantial impacts on the quality of life. Type 2 diabetes is one of the main causes of diabetic liver diseases with the most common being non‐alcoholic fatty liver disease. Several factors that may explain the mechanisms related to pathological and functional changes of diabetic liver injury include: insulin resistance, oxidative stress and endoplasmic reticulum stress. The realization that these factors are important in hepatocyte damage and lack of donor livers has led to studies concentrating on the role of stem cells (SCs) in the prevention and treatment of liver injury. Possible avenues that the application of SCs may improve liver injury include but are not limited to: the ability to differentiate into pancreatic β‐cells (insulin producing cells), the contribution for hepatocyte regeneration, regulation of lipogenesis, glucogenesis and anti‐inflammatory actions. Once further studies are performed to explore the underlying protective mechanisms of SCs and the advantages and disadvantages of its application, there will be a greater understand of the mechanism and therapeutic potential. In this review, we summarize the findings regarding the role of SCs in diabetic liver diseases.